Environmental consideration in flood mitigation and river restoration - Mohammed, Thamer Ahmed; Ghazali, Abdul Halim; Megat Mohd Noor, Megat Johari; Yusuf, Badronnisa (Faculty of Design & Architecture, Universiti Putra Malaysia, 2009)
In last decades, Malaysia is subjected to rapid development and as a result severe flooding has occurred particularly in urban areas. Flood mitigation measures were taken to reduce the flood damage and channel improvement is mainly used for this purpose. In the past, consultant engineers normally proposed a wider and deeper rectangular concrete river channel to mitigate the flood. This is because of the limited available river reserve and possibly the lack of environment awareness. The consequences of replacing the natural river channel with a concrete channel are reduction of aesthetic and recreational values of rivers and increased physical degradation including damaging the river ecosystem. Recently, there is a great emphasis to consider the environmental impact in canalizing rivers. In this study, the Malaysian experience in urban river restoration is highlighted with special emphasis on environmentally friendly materials installed for flood mitigation purposes